Effects of different artificial oxygen-supply systems on migrants' physical and psychological reactions in high-altitude tunnel construction. (February 2019) - Wang, Mingnian; Yan, Guanfeng; Yu, Li; Xie, Wenqiang; Dai, Yang
Abstract: The comfort and labor efficiency of plainsmen migrating from the plains to high-altitude areas to be engaged in intense physical work like tunnel construction could be affected by environmental parameters, especially oxygen content, and an artificial oxygen supply, such as an individual oxygen-supply system or a diffused oxygen-supply system, is required; however, the effectiveness of different oxygen-supply systems has rarely been systematically investigated. This study explored the effectiveness of individual oxygen-supply systems and diffused oxygen-supply systems considering migrants' physical and psychological reactions. Furthermore, the difference between various oxygen supply methods and how to select a proper method for different tunnel construction procedures are discussed. The survey was conducted in Balangshan Tunnel at an altitude of 3854 m in winter and included an individual oxygen-supply system experiment for three days and a diffused oxygen-supply system experiment for one day. Three plainsmen who grew up without any experiences of a high-altitude lifestyle were recruited. One of these participants did not use an artificial oxygen supply in the individual oxygen-supply system experiment and was considered the control group. Comparison of physical and psychological reactions between participants obtaining oxygen from different oxygen-supply systems and the control group aided in a systematic investigation of the effectiveness and features of different systems. The results showed that the trends of the physical responses of the participants with an artificial oxygen supply proved the reliability and practicability of both oxygen-supply systems compared with those of the control group, and there was no significant difference between the different systems. However, using an individual oxygen-supply system could make workers feel psychologically anxious due to the additional physical labor of carrying oxygen cylinders. This study indicates that selecting a proper oxygen-supply system for different tunnel construction procedures requires taking the features of the various systems into consideration for migrants moving from the plains to a high-altitude area. The results can be the basis for an oxygen-supply system design for tunnel construction personnel in high-altitude areas. Highlights: An overview of altitude stress all the world. assessing effectiveness of different oxygen-supply methods. Comparing different oxygen-supply methods in physical and psychological reactions of migrants. Presenting the factors that affects how to choose a proper oxygen-supply method in high-altitude tunnel construction.